Pengembangan Model Pembelajaran Bahasa Jawa SMP/MTs di Jawa Timur Berbasis Budaya Lokal - Setya Yuwono, (Widya Cendika, 2010)
This research is conducted on learning language culture paradigm. The approach used is learning language communicative and also constructivism one. Mean while the kind of research is development which has an orientation to develop of the process and to find result in detail, especially for the expected result, it has been evaluated. In this research, the expected result is learning language model for SMP/Mts in East Java which has innovation of local culture based. The Model of Learning Javanese Language which has Local Culture based is valid, effective and efficient by using syntax as follows: (a) cultural a-perception, (b) representation and discussion by applying the pattern of deeply thinking (berpikir menggalih) social interaction, (c) presentation and the result of working development, (d) the innovation of result cooperation in members of group discussion wis (n) Jawa, gak (n) Jawa, dan durung (n) Jawa, (e) the result of solve problem analysis and evaluation. This model has resulted learning requirements which consisted of Lesson Plan, Syllabus, students book, students worksheet, the result of test, and teachers guidance book.